Strategi Adaptasi Perubahan Iklim pada Kawasan Permukiman Berbasis Lahan Basah di Banjarmasin - Evan Elianto Supar; Humairoh Razak (Universitas Sebelas Maret Surakarta, 2024)
Climate change has had massive impacts, and various programs have been attempted. However, the community has not been impacted. Settlements are vulnerable objects and potentially become sustainable best practices. It is necessary to study the strategies for adaptation to climate change impacts on a residential area. This research aims to identify the relationship between adaptation strategies and a sustainable approach from Green Building Council Indonesia (GBCI) Neighbourhood V1.0. This research was conducted in the Karang Mekar Area, Banjarmasin City. This study uses a qualitative method through the stages of collection and analysis of data, restatement, and conclusion. The research found applied the strategy of 1) Using shading; 2) House and field level engineering, 3) Using solar panels, and 4) using The TOD concept.